Tissue typing the HLA-A locus from genomic DNA by sequence-specific PCR: comparison of HLA genotype and surface expression on colorectal tumor cell lines. - Browning, M; Krausa, P; Rowan, A; Bicknell, D; Bodmer, J; Bodmer, W (1993)
A system devised for tissue typing the HLA-A locus by PCR from genomic DNA has been used to investigate abnormalities of HLA expression in a panel of 30 colorectal tumor cell lines, by comparing the HLA-A locus genotype with surface expression of HLA. Three cell lines showed complete lack of HLA expression associated with failure to express beta 2-microglobulin. In two other cell lines, loss of expression of HLA-A2 was observed, in spite of the presence of the gene in genomic DNA. Eleven cell lines gave a single HLA-A locus specificity on PCR typing. In one of these cell lines we have demonstrated the loss of an HLA-A locus gene in the tumor cell by comparison with DNA from a lymphoblastoid B-cell line derived from the same patient. These data indicate that at least three independent mechanisms were involved in the loss of HLA expression on the colorectal tumor cell lines.